Modeling of the Disc Speed - Ab Ghani, Mohd Ruddin; Mohd Amin, Nur Huda; Kasdirin, Hyreil Anuar (2010)
This paper presents the modeling of the disc speed. The analysis and design of control systems for the modeling is assigned in leading computer solutions and linearized nonlinear systems.